Cartographies of pain: A study of chronotopes and contested bodies in Solzhenitsyn's early novels - Paoli, Natalie (My University, 2014)
My research aims to critically examine a particular kind of reality lived under the Stalinist era as portrayed in Alexander Solzhenitsyn’s early literary works, particularly One Day in the Life of Ivan Denisovich (1962), The First Circle (1968), and, Cancer Ward (1968), and to analyse how he offered a counter-narrative to the propagandistic view provided by the Stalinist regime, thereby challenging it. I will explore the extent to which Solzhenitsyn’s work can be seen as a manifestation of his commitment to keeping the past and memory alive by writing about it. What is highlighted in Solzhenitsyn’s works is the importance of memorialisation, of acknowledging and realising what happened in Russia during Stalin’s rule. There is a two-fold issue relating to this in his writing; firstly there is the problem of people not fully acknowledging the trauma they have experienced, and, secondly, there is the problem of complicity, of each citizen failing to acknowledge their guilt in what occurred. For Solzhenitsyn, no future would be possible for Russia until both of these concerns features have been exposed and dealt with. Alongside this is an awareness of the invariable inexpressibility of pain, as well as a concern with the respect that needs to be shown to the life stories of the victims. I will examine how Solzhenitsyn manages to convey Russia’s suffering during this period without it leading to the desensitisation of the reader.